Training Experience on Fair Trade and Agricultural Standards in Santa Elena, Ecuador - Garzozi-Pincay, René Faruk (2020)
This article, derived from the project called “Training and support for Fair Trade certification and the application of standards in agricultural-based production in the communes of Manglaralto and Colonche, province of Santa Elena, Ecuador”. In the agricultural production sector of the province of Santa Elena, as in all production, there are risks of not complying with current regulations; These risks can range from the exclusion of access to certain markets, to the fine for non-compliance with labor standards, to being sued in cases of physical harm caused to a person in the absence of safety standards, to the seizure of agricultural production in case of severe infractions and even imprisonment in some cases. The project aimed to make accessible to agricultural producers in Santa Elena, and to the applicable laws in their sector, guiding them towards legal compliance, informing them of the steps they can follow for homologation, and providing advice on how to avoid the state of non-compliance of such regulations, where the entire certification process is online.